2022
DOI: 10.21203/rs.3.rs-1300549/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, Practice and Barrier Towards Emergence Contraceptive Usage Among Female University Students at Kilimanjaro Region in Tanzania.

Abstract: Background: Unplanned pregnancy is major public health concern. Globally unintended pregnancies account for about 40% of all pregnancies annually. The problem is more in developed countries in which nearly half of all pregnancies are unintended. In Tanzania over 20 women die each day due to the complication of unplanned pregnancy and childbirth which contribute to high maternal mortality rate. Though EC can prevent unplanned pregnancies by nearly 95% to 99% but the practice is still very low in Africa as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…Formal education, 51.9% followed by the internet, 14.4%, and health facilities 12% were the common sources of information in a study done in Kilimanjaro among female university students. In the same study, it was proposed that multiple sources of information will aid in the wide dissemination of EC (Mariki et al, 2022). Additionally, a study conducted in Hai District showed that the most popular source of information was radio, 47.2% followed by newspapers 21.8%, television 18%, and the last friends 11.1% (Dangat & Njau, 2013).…”
Section: Knowledge Of Emergency Contraceptionmentioning
confidence: 99%
“…Formal education, 51.9% followed by the internet, 14.4%, and health facilities 12% were the common sources of information in a study done in Kilimanjaro among female university students. In the same study, it was proposed that multiple sources of information will aid in the wide dissemination of EC (Mariki et al, 2022). Additionally, a study conducted in Hai District showed that the most popular source of information was radio, 47.2% followed by newspapers 21.8%, television 18%, and the last friends 11.1% (Dangat & Njau, 2013).…”
Section: Knowledge Of Emergency Contraceptionmentioning
confidence: 99%